Lightweight high-wear-resistance composite material based on additive manufacturing and preparation method
Patent Information
- Application Number
- CN202311627901.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-11-30
AI Technical Summary
然而泡沫金属是利用发泡剂形成孔隙结构,泡沫金属骨架的孔隙率、孔隙的形状以及大小无法进行有效控制,且内部的孔隙不一定完全相联通
[0033]1、本发明利用极小曲面具有高的比表面积的特点,利用耐磨金属制备多孔耐磨骨架,增加树脂和耐磨金属的表面接触面积,提高结合性能。
Smart Images

Figure CN117601469B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coal mining machinery, specifically relating to a lightweight, high-wear-resistant composite material based on additive manufacturing and its preparation method. Background Technology
[0002] Wear resistance of the central trough of scraper conveyors has always been a significant challenge in coal mines and other mining engineering fields. This problem manifests primarily in the reduced service life and increased maintenance costs of the central trough due to long-term wear. This wear is often caused by the continuous friction and impact between the transported coal or other ore particles and the trough walls during transportation.
[0003] Traditionally, heavy metal materials such as wear-resistant steel plates have been used to improve the wear resistance of the conveyor's central trough. However, the use of these materials not only increases the overall weight of the conveyor, but the wear resistance of the steel plates is also limited. Since conveyors often need to be moved frequently in coal mining operations, their weight becomes a significant consideration. Therefore, reducing the weight of the conveyor's central trough while maintaining its good wear resistance has become a pressing problem for the industry.
[0004] Against this backdrop, researchers and engineers have begun actively exploring the possibilities of using lightweight materials such as resins. Resins, with their excellent wear resistance and impact resistance, have attracted considerable attention, making their introduction into the central trough section of scraper conveyors to prepare metal / resin composites a promising approach to improving conveyor performance. The research and application of this technology are expected to extend conveyor lifespan, reduce maintenance costs, and improve the efficiency of coal mining and ore transportation processes.
[0005] Current methods for preparing metal / resin composites include hot pressing, injection molding, extrusion, electrochemical deposition, coating, and laser 3D printing. Among these, hot pressing, injection molding, extrusion, and laser 3D printing all involve mixing metal and resin, with the resin acting as a binder. In these methods, the resin serves as the matrix, while the metal acts as reinforcing particles. Therefore, the resin content is relatively high, limiting its effectiveness in improving mechanical properties. Electrochemical deposition and surface coating involve coating metal onto a resin surface or vice versa. Composites prepared using these methods often suffer from low interfacial bonding strength.
[0006] Chinese patent document CN105799114A (201410841203.3) discloses a metal-resin composite, its manufacturing method, and its application. The metal-resin composite includes a metal matrix and a first resin material bonded to the surface of the metal matrix. The metal matrix includes a foamed metal skeleton and a second resin material filled within the foamed metal skeleton. The first resin material contains a first resin, and the second resin material contains a second resin. The surface of the metal matrix has a microporous structure. The microporous structure is formed by removing the foamed metal skeleton from the surface of the metal matrix, or by removing the second resin material from the surface of the metal matrix. A portion of the first resin material fills the microporous structure on the surface of the metal matrix and is integrated with the metal matrix. The metal-resin composite provided by the above patent has strong bonding between the metal matrix and the resin material layer. However, foamed metal uses a foaming agent to form a porous structure, and the porosity, shape, and size of the pores in the foamed metal skeleton cannot be effectively controlled, and the internal pores are not necessarily completely interconnected. In addition, the small specific surface area of the foam metal skeleton results in a small contact area between the metal and the resin, and a limited interfacial bonding force between the metal and the resin, which restricts the design of material properties. Summary of the Invention
[0007] The purpose of this invention is to provide a lightweight, high-wear-resistant composite material based on additive manufacturing and its preparation method. This invention utilizes the advantages of additive manufacturing of extremely small curved surface structures, such as easy control of porosity, pore size and shape, and large specific surface area of pore structure. It uses surfactants and the larger contact area of extremely small curved surfaces to prepare metal / resin composite materials with strong bonding ability and controllable performance.
[0008] To solve its technical problem, the present invention adopts the following technical solution: a method for preparing a lightweight, high-wear-resistant composite material based on additive manufacturing, comprising the following steps:
[0009] S1. A porous structure model with continuously varying porosity along a preset direction and interconnected pores is designed based on minimal surface units.
[0010] S2. Prepare porous wear-resistant materials using wear-resistant metal additive manufacturing;
[0011] S3. Perform surface-active treatment on the porous wear-resistant skeleton;
[0012] S4. Heat and melt the resin, then pour it into the porous wear-resistant skeleton;
[0013] S5. The porous wear-resistant skeleton, which has been poured with resin, is thermosetting to obtain a composite material. Thermosetting here refers to immersing the porous wear-resistant skeleton in molten resin, holding it for a certain period of time, and then allowing it to cool and solidify naturally to obtain a composite material. To improve the wear resistance of the composite material, a wear-resistant resin is preferred.
[0014] According to a preferred embodiment of the present invention, the porosity of the three-period minimal surface porous structure varies continuously as a cosine function or a sine function.
[0015] According to a preferred embodiment of the present invention, in step S5, the ratio of wear-resistant metal to resin on the outer surface of the composite material is at least 1:2 in terms of area ratio. By controlling the porosity of the porous structure model, the ratio of wear-resistant metal to resin on the outer surface of the final composite material is at least 1:2, ensuring both wear resistance and good toughness, making the composite material more impact-resistant.
[0016] According to a preferred embodiment of the present invention, in step S1, the porosity of the porous structure model skeleton is 10%-90%.
[0017] According to a preferred embodiment of the present invention, in step S1, the porosity of the porous structure model skeleton is 40%-90%.
[0018] According to a preferred embodiment of the present invention, in step S1, the porous wear-resistant skeleton is made of Ni60. Ni60 is an alloy powder, also known as nickel-based alloy powder, or nickel 60 in the industry. Nickel 60 + 35% tungsten carbide is a very good wear-resistant material with a hardness of HRC58-62.
[0019] According to a preferred embodiment of the present invention, in step S4, the resin is made of polytetrafluoroethylene (PTFE). Using PTFE resin provides better wear resistance.
[0020] According to a preferred embodiment of the present invention, in step S3, the surface activity treatment is carried out by immersion. The porous wear-resistant skeleton is immersed in a surfactant solution, which pours the surfactant solution into the pores of the porous wear-resistant skeleton. After immersion for a certain period of time, the porous wear-resistant skeleton is dried, thereby adsorbing a layer of surfactant on the surface of the porous structure.
[0021] According to a preferred embodiment of the present invention, in step S3, the surfactant used for surface activity treatment is an ammonium fluoride salt.
[0022] The present invention also discloses a lightweight, high-wear-resistant composite material based on additive manufacturing, which is prepared by the above-described method for preparing a lightweight, high-wear-resistant composite material based on additive manufacturing.
[0023] The inventive concept of this invention:
[0024] Layered materials formed by interlayers of wear-resistant metals and resins exhibit superior wear resistance, primarily due to several advantages: The hard-soft interlayer structure fully utilizes the properties of both materials, using the hard material to provide wear resistance, hardness, and abrasion resistance, while the soft material provides cushioning and shock absorption. This combined advantage results in superior wear resistance. The hard-soft interlayer structure reduces wear rate because, during wear, the hard layer bears the wear, while the soft layer provides cushioning and dispersion. This helps extend the material's service life and reduce maintenance costs. Superior impact resistance: The soft layer in the hard-soft interlayer structure has strong impact resistance, effectively absorbing impact energy and reducing the impact of external shocks on the material. This helps protect the hard layer, making it more wear-resistant. Overall, layered materials formed by hard-soft interlayers, through proper design, can maximize the advantages of both materials, providing superior wear resistance and making them suitable for engineering applications requiring exposure to high-wear environments.
[0025] Current resin / wear-resistant metal layered composite materials suffer from lower wear resistance in the resin layer, making the composite material more susceptible to wear. Therefore, forming a wear-resistant skeleton in the resin layer can significantly improve its wear resistance. This application utilizes additive manufacturing technology to design a skeleton with a gradient porosity, resulting in a resin layer with better wear resistance in the low-porosity region.
[0026] To fully leverage the performance advantages of resin and wear-resistant metal, form a layered composite material, and ensure a robust bond, this application introduces a porous scaffold design with continuously varying micro-curved pore sizes and employs surfactants to prepare a layered resin / wear-resistant metal composite material.
[0027] By using a porous scaffold design with continuously varying porosity through extremely small curved surfaces, a porosity variation of 10%-90% can be achieved. Therefore, a layered gradient composite material with a resin content of 90%-10% can be realized.
[0028] In the composite process of metal and resin, the bonding area between the two is a key factor, directly affecting their bonding ability and performance. To achieve a stronger bond, a three-period minimal surface structure is introduced as a control model. This model has many unique mathematical parameters, and its most significant features are: firstly, a large surface area; secondly, precise control over the pore size, shape, and porosity; and thirdly, the internal pores of this structure are continuously interconnected, allowing the resin to achieve orderly bonding with the skeleton. The resin within each pore connects to form a whole, which is beneficial to improving the overall performance of the composite material. Therefore, using a three-period minimal surface structure can effectively improve the bonding strength between metal and resin.
[0029] This invention effectively improves the bonding ability between metals and resins by employing a three-period minimal curved surface structure to increase the surface area of the bonding interface. Its unique structure allows for more contact points and interaction surfaces, thereby promoting a stronger bond. This method of increasing the bonding area helps improve the overall performance of the composite material, including strength, stability, and wear resistance, making it more suitable for various engineering applications. This is an important and effective method for preparing metal-resin composite materials.
[0030] Due to the different chemical properties of metals and resins, their direct bonding performance is relatively poor, and the strength of a pure resin layer is low. This invention uses a surfactant to treat the surface of the porous scaffold, reducing its surface tension and improving the wettability of both the metal and resin materials, making them easier to adhere to each other. The surfactant also increases the bond strength between the two materials, improving their bonding performance. By introducing the surfactant, a tighter bond between the metal and resin is achieved, ensuring the stability and reliability of the composite material; it plays a crucial role at the metal-resin interface.
[0031] The method of this invention achieves an ideal balance between lightweight properties and wear resistance in resin / metal composites, providing a high-performance solution for a variety of applications, especially where weight reduction is required.
[0032] Compared with the prior art, the beneficial effects of the present invention are:
[0033] 1. This invention utilizes the characteristic of extremely small curved surfaces having high specific surface area to prepare a porous wear-resistant skeleton using wear-resistant metal, thereby increasing the surface contact area between the resin and the wear-resistant metal and improving the bonding performance.
[0034] 2. By designing a porous support model with a minimum curved surface structure in which the porosity changes continuously in a predetermined direction and the pores are interconnected, a layered composite material with alternating contents of resin and wear-resistant metal is realized. By utilizing the wear-resistant properties of the wear-resistant metal and the buffering performance of the resin, the advantages of the layered composite material are fully utilized, and the overall performance of the resin / metal composite material is improved.
[0035] 3. This invention also utilizes surfactants to improve the bonding force between the resin and the wear-resistant metal, thereby further improving the overall performance of the resin / metal composite material. Attached Figure Description
[0036] Figure 1 This is a schematic diagram illustrating the process of adding ammonium fluoride surfactant in an embodiment of the present invention;
[0037] Figure 2 This is a schematic diagram of the melting and infiltration process of polytetrafluoroethylene in an embodiment of the present invention. Detailed Implementation
[0038] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention.
[0039] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a lightweight, high-wear-resistant composite material based on additive manufacturing, comprising a three-period, continuously varying porous support structure with minimal curved surface porosity, additive manufacturing of wear-resistant Ni60, addition of surfactant, and melt infiltration of polytetrafluoroethylene.
[0040] S1. The method for constructing a three-period minimal surface structure includes the following steps:
[0041] The three-period minimal surface porous support structure is formed by stacking multiple basic units in three dimensions. These basic units are constructed based on a three-period minimal surface. The porosity of the porous support structure changes continuously according to a cosine or sine function, and the pores are interconnected. In this embodiment, the prepared layered composite material is used to fabricate the middle trough of a scraper conveyor. Therefore, the porosity of the porous structure model in the planar direction is designed to change continuously in a gradient along the scraper running direction on the upper surface, forming a flat gradient support. This reduces weight while making it more wear-resistant and possessing excellent toughness, which helps improve the impact resistance of the product.
[0042] (1) First, the equations of the three basic units P, G and D of the minimal surfaces are:
[0043]
[0044] In the above three equations, T is the period of the minimal surface, which corresponds to the size of the structural unit; C is the value of adjusting the porosity of the porous support structure; the relationship between the C value corresponding to the three minimal surface structures and the porosity P of the porous support structure is shown in equations (4)-(6) below:
[0045] P P =0.2837×C+0.5#(4)
[0046] P G =0.3287×C+0.5#(5)
[0047] P D =0.5872×C+0.5#(6)
[0048] (2) The porosity of the gradient scaffold is related to the C value. The C value is transformed into a function related to the Cartesian coordinate value, as shown in equation (7):
[0049] C = f C (x,y,z)#(7)
[0050] (3) Construct a gradient porous scaffold, where the porosity varies only along the X direction. Therefore, the C function can be simplified to a function that depends only on the X coordinate. Based on this, the cosine function is selected as the C function model, as shown in Equation (8). By adjusting the parameters in the function, the gradient of the porosity of the porous scaffold can be continuously varied.
[0051]
[0052] In equation (8), r = x, x is a direction in space, m controls the amplitude of the C function change, n controls the position of the C function, and t controls the period of the C function; by adjusting the three parameters m, n, and t, the gradient change of the porosity of the porous support can be controlled.
[0053] (4) Determine the diameter, height, average porosity, and period of porosity variation along the radius of the variable gradient porous support structure. Then, combine equations (7) and (8) to obtain the final expression for the variable gradient porous support:
[0054]
[0055]
[0056]
[0057] (5) The structural design formulas of three minimal surfaces are obtained through the above steps. Mathematical models with porosity of 40%-90% are generated using the mathematical modeling software Mathematica. After repair, porous support structure samples are processed.
[0058] Additive manufacturing of S2 and wear-resistant Ni60
[0059] First, Ni60 alloy powder was prepared using an aerosol method. Then, a porous wear-resistant skeleton was fabricated using an SLM 125HL selective laser melting system. This system is equipped with an IPG fiber optic cable with a maximum power of 400W; the powder feeding method is top-feed; the spot diameter is 70–100 μm; and the maximum scanning speed is 10 m / s. The specific printing parameters for the Ni60 skeleton were: powder layer thickness 20 μm, scanning spacing 60–100 μm, scanning speed 400–1200 mm / s, and laser power 100–300 W.
[0060] Before printing, the model of the porous wear-resistant skeleton is imported into the printing equipment. The equipment then prints layer by layer using a powder-laying and printing principle. During the forming process, the first layer of alloy powder is laid on the substrate using a bidirectional powder-laying method. The equipment then divides each cross-section of the model into 4mm wide strips, which are scanned one by one by a laser beam from a fiber optic receiver. The scan proceeds along one scanning path first, then at a set interval, until the scanning of that layer is complete. After the first layer of powder melts, cools, and solidifies, the strip division direction is rotated 67° on the second layer, and scanning is performed according to predetermined parameters. This 67° rotation scanning strategy between powder layers effectively reduces the composite zone between the upper and lower molten pools, weakening the accumulation of internal stress along the structural direction. This layer-by-layer scanning is continued until the model is formed. High-purity argon gas is used as a protective gas to prevent powder oxidation.
[0061] The addition of S3 and ammonium fluoride surfactants
[0062] First, ensure that the surface of the porous wear-resistant skeleton is clean, dust-free, and free of visible dirt or grease. Typically, solvent cleaning or ultrasonic cleaning is used to clean the surface of the porous wear-resistant skeleton.
[0063] Preparation of ammonium fluoride salt solutions: Prepare solutions of ammonium fluoride salt surfactants. These solutions are typically prepared in organic solvents such as ethanol or acetone. Ensure that the solution is prepared according to the manufacturer's recommendations. Organic solvents dissolve the surfactant more readily, achieving a more uniform distribution of the surfactant within the backbone.
[0064] Immersion and coating: such as Figure 1 As shown, the porous wear-resistant skeleton is immersed in an ammonium fluoride solution, ensuring the entire surface is covered. The immersion time varies depending on the needs, typically ranging from several minutes to several hours. After immersion, the porous wear-resistant skeleton is removed and allowed to air dry or dried using an airflow.
[0065] Drying: Place the impregnated porous wear-resistant skeleton in an oven and dry it at an appropriate temperature. This helps to remove organic solvents and allows ammonium fluoride surfactants to adhere to the surface of the skeleton.
[0066] S4, Melting and Infiltration of Polytetrafluoroethylene
[0067] Soaking: such as Figure 2As shown, PTFE or PTFE powder is placed in a container and heated to melt. The printed porous wear-resistant skeleton is then immersed in the molten PTFE using a lifting device. The melt is repeatedly turned or stirred to ensure that the PTFE completely enters the porous skeleton. To improve preparation efficiency, the container cavity can be matched to the shape of the porous wear-resistant skeleton, ensuring that the melt does not completely submerge the skeleton, reducing subsequent processing work. Because molten PTFE has good fluidity, the porous wear-resistant skeleton can be directly immersed in the molten PTFE, which automatically fills the internal pores of the skeleton.
[0068] S5. Thermosetting: The porous wear-resistant skeleton filled with PTFE is thermoset at an appropriate temperature to obtain a composite material. The surface of the resulting composite material can be treated to remove excess resin material. This will help the PTFE bond to the skeleton surface and provide durable adhesion.
[0069] Advantages of the embodiments of the present invention:
[0070] This invention is based on three typical unit structures (P, G and D) of three-period minimal curved surfaces to construct a porous structure model skeleton with continuously varying porosity. The porosity is controlled between 10% and 90%, and it has a large surface area, thereby improving the bonding strength between metal and resin. In addition, the pores in this structure are interconnected, which helps the resin in the composite material to form a whole, which is beneficial to improving the overall performance of the composite material.
[0071] Since wear-resistant metal Ni60 and lightweight, wear-resistant, and impact-resistant polytetrafluoroethylene (PTFE) are two high-performance materials, their combination can produce lightweight wear-resistant metal / resin composites. Composites with alternating resin and wear-resistant metal layers offer significant advantages in improving the wear resistance of the composite material. However, due to their different chemical properties, the direct bonding performance between the two is relatively poor, and the strength of the pure resin layer is relatively low.
[0072] Ammonium fluoride salts are surfactants that play a crucial role at the interface between metals and resins. Specifically, ammonium fluoride salts can reduce surface tension, improve the wettability of the two materials, and make them easier to adhere to each other. This surfactant can also increase the bond strength between the two materials, improving their bonding performance. By introducing ammonium fluoride salts, a tighter bond can be achieved between Ni60 and PTFE, ensuring the stability and reliability of the composite material. Other suitable surfactants can also be selected.
[0073] The wear-resistant skeleton was then fabricated using additive manufacturing technology and Ni60 alloy. A layer of ammonium fluoride surfactant was then adsorbed onto the porous structure surface via an immersion method. Finally, polytetrafluoroethylene (PTFE) was cast into the Ni60 wear-resistant metal skeleton using a melt infiltration method (casting method). This involved heating the PTFE to create a fluid state, then casting it into a gradient support, followed by cooling to obtain the composite material. This method significantly reduces the overall weight of the composite material by using lightweight, wear-resistant PTFE instead of the wear-resistant metal. Furthermore, the surfactant achieves a good bond between the wear-resistant metal and the resin, and the significant difference in resin content between the low-porosity and high-porosity regions creates a layered composite material, improving its overall performance.
Claims
1. A method for preparing a layered composite material based on additive manufacturing, characterized in that, The process for preparing the middle trough of a scraper conveyor includes the following steps: S1. A porous structure model is designed based on a three-period minimal surface unit, in which the porosity changes continuously in a gradient along the scraper running direction on the upper surface of the central groove and the pores are interconnected; the porosity of the porous structure model changes continuously as a cosine function or a sine function. The porosity of the porous structure model is 10%-90%. Through the design of a porous scaffold with continuously varying porosity through extremely small curved holes, the porosity can be varied from 10% to 90%, thus achieving a layered gradient composite material with a resin content of 90%-10%. S2. A porous wear-resistant skeleton was prepared using wear-resistant metal Ni60 via selective laser melting additive manufacturing technology. In step S2, the printing parameters for selective laser melting are: powder layer thickness 20μm, scanning spacing 60-100μm, scanning speed 400-1200mm / s, laser power 100-300W, and the scanning direction between adjacent powder layers rotated by 67°. S3. The porous wear-resistant skeleton is surface-actively treated by immersion method, and the surfactant for surface-active treatment is ammonium fluoride salt. S4. Heat and melt the polytetrafluoroethylene resin, then immerse the porous wear-resistant skeleton in the molten resin using a lifting device. During the immersion process, repeatedly turn or stir the melt to ensure that the molten resin completely fills the porous wear-resistant skeleton. S5. The porous wear-resistant skeleton filled with resin is thermo-cured to obtain a layered composite material; the ratio of wear-resistant metal to resin on the outer surface of the composite material is at least 1:2 according to the area ratio.
2. The method for preparing a layered composite material based on additive manufacturing according to claim 1, characterized in that: In step S1, the porosity of the porous structure model is 40%-90%.
3. The method for preparing a layered composite material based on additive manufacturing according to claim 1, characterized in that: In step S1, the three-period minimum surface is a P-type, G-type, or D-type minimum surface.
Citation Information
Patent Citations
Porous foam metal based embedded type solid self-lubricating composite material and preparation method thereof
CN101906549A
Preparation method of porous aluminum coating polytetrafluoroethylene film
CN109433566A
Foam-filled three-period minimum-curved-surface porous structure sandwich panel and preparation method thereof
CN110641083A